Lithium ion gel electrolyte, preparation method and application
By introducing specific polymer monomer structures into the gel electrolyte of lithium-ion batteries, with -F, -OSi(CnH2n+1)3 and -Si(CmH2m+1)3, the material damage caused by volume expansion of silicon-based anode materials during charging and discharging is solved, which significantly improves the chemical stability and mechanical properties of the battery and extends the cycle life of the battery.
Patent Information
- Application Number
- CN202411334480.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-03-14
AI Technical Summary
In existing lithium-ion batteries, the silicon-based negative electrode material has volume expansion problems during charging and discharging, resulting in material cracks, powdering and rapid attenuation of battery capacity. At the same time, there is still room for improvement in chemical stability, thermal stability and mechanical properties of gel electrolyte.
A lithium ion gel electrolyte is used, which includes a specific polymer monomer structure with -F, -OSi(CnH2n+1)3 and -Si(CmH2m+1)3. These functional groups promote the formation of SEI films and improve the chemical stability and mechanical properties of the battery. The preparation method includes preparing a polymer monomer, dissolving a lithium salt, a film forming agent, a heat initiator and a polymer monomer in an organic solvent, then injecting it into a battery cell and performing hot pressing to initiate polymerization.
By introducing -F, -OSi(CnH2n+1)3 and -Si(CmH2m+1)3, the interface stability, mechanical strength and chemical stability of the battery are significantly improved, thereby improving the circulation performance and storage performance of lithium-ion batteries and extending the cycle life of the battery.
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium ion battery electrolyte preparation, and in particular to a lithium ion gel electrolyte, a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries have become the main power source for portable electronic devices, electric vehicles and energy storage systems due to their high energy density, long cycle life and low self-discharge rate. As the requirements for battery energy density continue to increase, silicon-based materials have become one of the most promising alternatives to graphite anode materials due to their extremely high theoretical specific capacity (about 4200mAh / g).
[0003] However, silicon-based negative electrode materials have the problem of volume expansion during the charging and discharging process. Volume expansion will cause cracks in silicon-based negative electrode materials and even pulverize them, destroying the contact between the electrode material and the current collector, causing the active material to separate from the electrode sheet, and causing the battery capacity to decay rapidly.
[0004] The polymer matrix with a mesh structure in the polymer gel electrolyte is distributed between the particles of the battery pole piece, which alleviates the material cracking and pulverization problems caused by volume expansion and contraction between the particles. It can also eliminate the battery leakage problem and improve the physical hardness of the soft-pack battery, thereby improving the safety and stability of the battery. However, the existing gel electrolyte materials still have room for improvement in chemical stability, thermal stability and mechanical properties. Summary of the invention
[0005] In view of the technical problems existing in the prior art, the present invention aims to provide a lithium ion gel electrolyte, a preparation method and an application thereof.
[0006] One of the purposes of the present invention is to provide a lithium ion gel electrolyte, the lithium ion gel electrolyte comprising the following raw materials in parts by weight:
[0007]
[0008]
[0009] Wherein, the polymer monomer structure is shown in formula (1):
[0010]
[0011] R includes -F, -Si(OC n H 2n+1 )3 or -Si(C m H 2m+1 )3; n=1~3, m=0~3.
[0012] Preferably, the polymer monomer is at least one of the following compounds:
[0013]
[0014]
[0015] Preferably, in the polymer monomer structure, n=1, m=1.
[0016] Preferably, the lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluorophosphoryl)imide, lithium difluorooxalatoborate, lithium bisoxalatoborate, lithium difluorophosphate, lithium hexafluorophosphate or lithium tetrafluoroborate.
[0017] Preferably, the organic solvent comprises one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, ethyl propionate, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-dimethoxyethane, acetone, acetonitrile, methyl acetate, ethyl acetate, methyl propionate, tetrahydrofuran or 2-methyltetrahydrofuran.
[0018] Preferably, the organic solvent comprises ethylene carbonate and ethyl methyl carbonate.
[0019] Preferably, the organic solvent comprises ethylene carbonate and ethyl methyl carbonate in a ratio of 3:7.
[0020] Preferably, the film former includes one or more of vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, lithium difluorophosphate or lithium difluorooxalatoborate.
[0021] Preferably, the thermal initiator includes any one or more of azobisisobutyronitrile, dibenzoyl peroxide, di(4-tert-butylcyclohexyl)peroxydicarbonate, dodecanoyl peroxide or diisopropyl peroxydicarbonate.
[0022] A second object of the present invention is to provide a method for preparing a lithium ion gel electrolyte, the preparation method comprising:
[0023] S1 Preparation of polymer monomers
[0024] An organic solvent, pentaerythritol tetraacrylate and sodium trifluoromethanesulfinate are added to a three-necked flask in sequence, and copper salt is then added under stirring. Tert-butyl peroxide (TBHP, 70% aqueous solution) is then slowly added dropwise. The addition is completed within 30 minutes. The reaction is carried out at 80-90° C. for 5 hours to obtain a polymer monomer as shown in formula (9).
[0025] Pentaerythritol is added to the reactor, and then trimethylsilyl chloride, triethylsilyl chloride or tripropylsilyl chloride is added, and p-toluenesulfonic acid and cyclohexane are added as catalysts. The reaction is carried out at 85-90° C. to generate trimethylpentaerythritol tetrapropylene silane product, as shown in formula (2), formula (3) or formula (4).
[0026] (CnH 2n+1 )3SiOCH3 is continuously dripped into the aqueous solution of pentaerythritol tetraacrylate, and ammonium persulfate solution is added dropwise in a water bath at 80°C, and the dripping speed is controlled to be about 30 minutes to complete the dripping, and the temperature is kept constant for 4 hours. The reaction is completed to obtain an organosiloxane-modified product, as shown in Formula 5, Formula 6, Formula 7 or Formula 8, (CnH 2n+1 )3SiOCH3 includes methoxytrimethylsilane, methoxytriethylsilane, methoxytriethylsilane or methoxytriisopropylsilane;
[0027] S2 dissolving lithium salt, film-forming agent, thermal initiator and polymer monomer in an organic solvent to obtain a mixed solution;
[0028] S3 injects the mixed solution into the battery cell, and after standing still, performs heat pressing to initiate polymerization.
[0029] Preferably, the standing time is 40 to 50 hours; and the hot pressing polymerization is performed in a chemical forming cabinet at 70 to 90° C. for 0.2 to 1 hour.
[0030] The third object of the present invention is to provide an application of a lithium ion gel electrolyte, characterized in that the lithium ion gel electrolyte can be used to prepare a silicon negative electrode battery.
[0031] Preferably, the process of preparing a silicon negative electrode battery includes:
[0032] The battery containing the gel electrolyte in the cell of step S3 is placed at room temperature and then subjected to conventional formation, high temperature aging, vacuum pumping and capacity separation, and finally battery packaging to obtain a finished lithium-ion silicon negative electrode battery.
[0033] Preferably, conventional formation includes charging at 0.1C current for 60 minutes, and then charging at 0.2C current to an upper voltage limit of 3.8V; the aging temperature is 40-50°C, the time is 20-30 hours, the vacuum degree of vacuum pumping is 70-100 kPa, and the vacuum pumping time is 3-10 seconds.
[0034] Beneficial effects of the present invention:
[0035] The present invention provides a lithium ion gel electrolyte, wherein the polymer monomer is a monomer having -F, -OSi(C n H 2n+1 )3 and -Si(C m H 2m+1 )3 of tetrapentaerythritol tetraacrylate.
[0036] In the present invention, -F has extremely high electronegativity, which can increase the chemical corrosion resistance and oxidation resistance of the polymer, thereby improving the chemical stability of the electrolyte. At the same time, fluorine-containing polymers usually have good thermal stability, so that the gel electrolyte can maintain its performance under high temperature environment, and -F can reduce the surface energy of the polymer, improve the wettability and ionic conductivity of the electrolyte, thereby improving the electrochemical performance of the battery. -F also has a lower dielectric constant, which helps to reduce the dielectric loss of the electrolyte and improve the efficiency of the battery.
[0037] -OSi(C n H 2n+1 )3 and -Si(C m H 2m+1 )3 has a high bond energy, which can promote the formation of a uniform and dense SEI film during the charge and discharge process, preventing adverse chemical reactions between the electrolyte and the electrode material. n H 2n+1 )3 and -Si(C m H 2m+1 )3 helps to form a cross-linked structure, thereby enhancing the mechanical strength and flexibility of the gel electrolyte.
[0038] -OSi(C n H 2n+1 )3 and -Si(C m H 2m+1 )3 has excellent flexibility and elasticity, which can provide a buffering effect during the volume changes of the electrode material (such as expansion and contraction during charging and discharging), reduce the damage to the electrode structure caused by mechanical stress, and extend the cycle life of the battery.
[0039] By introducing -F, -OSi(C n H 2n+1 )3 and -Si(C m H 2m+1 )3, -F and -OSi(C n H 2n+1 )3 and -Si(C m H 2m+1 )3 can significantly improve the battery's interface stability, mechanical strength and chemical stability at the microscopic level, thereby effectively improving the cycle performance and storage performance of lithium-ion batteries. DETAILED DESCRIPTION
[0040] According to the first aspect of the present invention, a lithium ion gel electrolyte is provided, wherein the lithium ion gel electrolyte comprises the following raw materials in parts by weight:
[0041]
[0042] Wherein, the polymer monomer structure is shown in formula (1):
[0043]
[0044] R includes -F, -OSi(C n H 2n+1 )3 or -Si(C m H 2m+1 ) One or more of 3;
[0045] n=1~3, m=0~3.
[0046] In the present invention, -F has extremely high electronegativity and chemical stability, -OSi(C n H 2n+1 )3 and -Si(CH2) m C2H3 has a high bond energy. During the chemical formation process, -F and -OSi(C n H 2n+1 )3 and -Si(C m H 2m+1 )3 can promote the formation of a uniform and dense SEI film, which can prevent the electrolyte from further reacting with the electrode, reduce the occurrence of side reactions, further improve the interfacial stability of the electrode material, help reduce the formation of lithium dendrites, and prevent mechanical damage to the electrode material, thereby increasing the cycle life of the battery.
[0047] -F's extremely high electronegativity can increase the polymer's chemical corrosion resistance and oxidation resistance, thereby improving the chemical stability of the electrolyte. At the same time, fluorinated polymers usually have good thermal stability, allowing the gel electrolyte to maintain its performance under high temperature conditions, and -F can reduce the surface energy of the polymer, improve the wettability and ionic conductivity of the electrolyte, thereby improving the electrochemical performance of the battery. -F also has a lower dielectric constant, which helps reduce the dielectric loss of the electrolyte and improve the efficiency of the battery.
[0048] And-OSi(C n H 2n+1 )3 and -Si(C m H 2m+1 )3 chain has excellent flexibility and elasticity, which can provide buffering effect in the volume change of electrode materials (such as expansion and contraction during charging and discharging), reduce the damage of mechanical stress to the electrode structure, and extend the cycle life of the battery. n H 2n+1 )3 and -Si(C m H 2m+1)3's chain structure helps maintain the ionic conductivity of the electrolyte and improves the overall performance of the battery. The silane group significantly enhances the mechanical strength and interfacial adhesion of the electrode material by covalently bonding with the electrode material. This enhanced mechanical property helps maintain the integrity of the electrode structure and reduces electrode rupture during charge and discharge. The introduction of the silane group improves the chemical stability of the electrode surface and reduces the side reactions between the electrolyte and the electrode material, thereby improving the cycle stability of the battery. And -OSi(C n H 2n+1 )3 and -Si(C m H 2m+1 )3 helps to form a cross-linked structure, thereby enhancing the mechanical strength and flexibility of the gel electrolyte.
[0049] By introducing -F, -OSi(C n H 2n+1 )3 and -Si(C m H 2m+1 )3, can significantly improve the battery's interface stability, mechanical strength and chemical stability at the microscopic level, thereby effectively improving the cycle performance and storage performance of lithium-ion batteries.
[0050] In the present invention, in the polymer monomer structure, n is, for example, 1, 2 or 3; m is, for example, 1, 2 or 3.
[0051] In the present invention, the weight of the lithium salt is, for example, 10 parts, 11 parts, 12 parts, 12.5 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts or 20 parts.
[0052] In the present invention, the weight of the organic solvent is, for example, 70 parts, 72 parts, 74 parts, 76 parts, 78 parts, 80 parts, 82 parts, 84 parts, 86 parts, 88 parts or 90 parts.
[0053] In the present invention, the film-forming agent can form a stable and uniform solid electrolyte interface (SEI) film on the electrode surface, effectively preventing the solvent molecules and other electrolyte components in the electrolyte from reacting with the electrode material, significantly improving the cycle life of the battery, improving the safety of the battery, improving the storage performance and reducing the interface resistance. The weight of the film-forming agent is, for example, 0.5 parts, 1 part, 1.5 parts, 2 parts, 2.5 parts, 3 parts, 3.5 parts or 4 parts.
[0054] In the present invention, the main function of the thermal initiator in the lithium ion battery gel electrolyte is to start the polymerization reaction, control the polymerization rate and improve the uniformity of the electrolyte. The weight of the thermal initiator is, for example, 0.05 parts, 0.06 parts, 0.07 parts, 0.08 parts, 0.09 parts, 0.10 parts, 0.11 parts, 0.12 parts, 0.13 parts, 0.14 parts or 0.15 parts.
[0055] In the present invention, the weight of the polymer monomer is, for example, 0.1 parts, 0.3 parts, 0.5 parts, 0.7 parts, 1 parts, 1.3 parts, 1.5 parts, 2 parts, 2.5 parts or 3 parts.
[0056] In a preferred embodiment of the present invention, the polymer monomer is at least one of the following compounds:
[0057]
[0058]
[0059] In a preferred embodiment of the present invention, in the polymer monomer structure, n=1, m=1.
[0060] In a preferred embodiment of the present invention, the lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluorophosphoryl)imide, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorophosphate, lithium hexafluorophosphate or lithium tetrafluoroborate.
[0061] In the present invention, the lithium salt is, for example, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluorophosphoryl)imide, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorophosphate, lithium hexafluorophosphate, lithium tetrafluoroborate, lithium bis(trifluoromethanesulfonyl)imide and lithium bis(trifluorophosphoryl)imide, lithium difluorooxalatoborate and lithium dioxalatoborate, lithium dioxalatoborate and lithium difluorophosphate, lithium difluorophosphate and lithium hexafluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate and lithium difluorophosphate, lithium difluorophosphate, lithium hexafluorophosphate and lithium tetrafluoroborate, or a combination of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluorophosphoryl)imide and lithium difluorooxalatoborate.
[0062] In a preferred embodiment of the present invention, the organic solvent includes one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, ethyl propionate, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-dimethoxyethane, acetone, acetonitrile, methyl acetate, ethyl acetate, methyl propionate, tetrahydrofuran or 2-methyltetrahydrofuran.
[0063] In the present invention, the organic solvent is, for example, ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, ethyl propionate, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-dimethoxyethane, acetone, acetonitrile, methyl acetate, ethyl acetate, methyl propionate, tetrahydrofuran, 2-methyltetrahydrofuran, ethylene carbonate and ethyl methyl carbonate, ethylene carbonate and propylene carbonate, dimethyl carbonate and diethyl carbonate, ethyl methyl carbonate and ethyl acetate, ethylene carbonate, diethyl carbonate and ethyl methyl carbonate, or a combination of ethyl methyl carbonate, ethyl acetate and ethyl propionate.
[0064] Preferably, the organic solvent comprises ethylene carbonate and ethyl methyl carbonate;
[0065] Preferably, the organic solvent comprises ethylene carbonate and ethyl methyl carbonate in a ratio of 3:7.
[0066] In a preferred embodiment of the present invention, the film-forming agent includes one or more of vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, lithium difluorophosphate or lithium difluorooxalatoborate.
[0067] In the present invention, the positive electrode film-forming agent is, for example, vinylene carbonate, lithium difluorophosphate, lithium difluorooxalatoborate, vinylene carbonate and lithium difluorophosphate, lithium difluorophosphate and lithium difluorooxalatoborate, or a combination of vinylene carbonate, lithium difluorophosphate and lithium difluorooxalatoborate.
[0068] In a preferred embodiment of the present invention, the thermal initiator includes any one or more of azobisisobutyronitrile, dibenzoyl peroxide, di(4-tert-butylcyclohexyl)peroxydicarbonate, dodecanoyl peroxide or diisopropyl peroxydicarbonate.
[0069] In the present invention, the thermal initiator is, for example, azobisisobutyronitrile, dibenzoyl peroxide, di(4-tert-butylcyclohexyl)peroxydicarbonate, dodecanoyl peroxide, diisopropyl peroxydicarbonate, azobisisobutyronitrile and dibenzoyl peroxide, dibenzoyl peroxide and di(4-tert-butylcyclohexyl)peroxydicarbonate, or a combination of azobisisobutyronitrile, dibenzoyl peroxide and di(4-tert-butylcyclohexyl)peroxydicarbonate.
[0070] According to the second aspect of the present invention, a method for preparing a lithium ion gel electrolyte is provided, the preparation method comprising:
[0071] S1 Preparation of polymer monomers
[0072] An organic solvent, pentaerythritol tetraacrylate and sodium trifluoromethanesulfinate are added to a three-necked flask in sequence, and copper salt is then added under stirring. Tert-butyl peroxide (TBHP, 70% aqueous solution) is then slowly added dropwise. The addition is completed within 30 minutes. The reaction is carried out at 80-90° C. for 5 hours to obtain a polymer monomer as shown in formula (9).
[0073] Pentaerythritol is added to the reactor, and then trimethylsilyl chloride, triethylsilyl chloride or tripropylsilyl chloride is added, and p-toluenesulfonic acid and cyclohexane are added as catalysts. The reaction is carried out at 85-90° C. to generate trimethylpentaerythritol tetrapropylene silane product, as shown in formula (2), formula (3) or formula (4).
[0074] (CnH 2n+1 )3SiOCH3 is continuously dripped into the aqueous solution of pentaerythritol tetraacrylate, and ammonium persulfate solution is added dropwise in a water bath at 80°C, the dripping speed is controlled to be about 30 minutes, and the dripping is completed at a constant temperature and stirred for 4 hours. The reaction is completed to obtain an organosiloxane-modified product, as shown in Formula 5, Formula 6, Formula 7 or Formula 8;
[0075] (CnH 2n+1 )3SiOCH3 includes methoxytrimethylsilane, methoxytriethylsilane, methoxytriethylsilane or methoxytriisopropylsilane;
[0076] S2 dissolving lithium salt, film-forming agent, thermal initiator and polymer monomer in an organic solvent to obtain a mixed solution;
[0077] S3 injects the mixed solution into the battery cell, and after standing still, performs heat pressing to initiate polymerization.
[0078] In the present invention, the thermal compression polymerization is to form a battery containing a gel electrolyte in the battery cell, thereby reducing the presence of liquid electrolyte and improving the thermal safety of the battery.
[0079] In a preferred embodiment of the present invention, the standing time is 40 to 50 hours; and the hot pressing polymerization is performed in a chemical forming cabinet at 70 to 90° C. for 0.2 to 1 hour.
[0080] In the present invention, the standing time is, for example, 40h, 41h, 42h, 43h, 44h, 45h, 46h, 47h, 48h, 49h or 50h. The hot pressing polymerization temperature is, for example, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or 90°C. The hot pressing time is, for example, 0.2h, 0.4h, 0.6h, 0.8h, 1.0h, 2h.
[0081] In the present invention, the organic solvent in step S1 includes acetonitrile, dichloromethane or trifluoroethanol.
[0082] In the present invention, the copper salt in step S1 includes cupric acetate, cuprous chloride or cuprous bromide.
[0083] In the present invention, the concentration of the ammonium persulfate solution in step S1 is 1% to 10%.
[0084] According to the third aspect of the present invention, an application of a lithium ion gel electrolyte is provided, and the lithium ion gel electrolyte can be used to prepare a silicon negative electrode battery.
[0085] In a preferred embodiment of the present invention, the process of preparing a silicon negative electrode battery includes:
[0086] The battery containing the gel electrolyte in the cell of step S3 is placed at room temperature and then subjected to conventional formation, high temperature aging, vacuum pumping and capacity separation, and finally battery packaging to obtain a finished lithium-ion silicon negative electrode battery.
[0087] In a preferred embodiment of the present invention, conventional formation includes charging at 0.1C current for 60 minutes, and then charging at 0.2C current to a voltage upper limit of 3.8V; the aging temperature is 40-50°C, the time is 20-30 hours, the vacuum degree of vacuum pumping is 70-100 kPa, and the vacuum pumping time is 3-10 seconds.
[0088] In the present invention, the aging temperature is, for example, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C or 50°C. The aging time is, for example, 20h, 21h, 22h, 23h, 24h, 25h, 26h, 27h, 28h, 29h or 30h. The vacuum degree is, for example, 70kPa, 75kPa, 80kPa, 85kPa, 90kPa, 95kPa or 100kPa. The vacuum pumping time is, for example, 3s, 4s, 5s, 6s, 7s, 8s, 9s or 10s.
[0089] Example 1
[0090] S1 Preparation of a polymer monomer as shown in formula (9)
[0091] In a three-necked flask, 20 mL of an organic solvent, 0.1 mol of pentaerythritol tetraacrylate, and 0.4 mol of sodium trifluoromethanesulfinate were added in sequence, and then 0.5 g of copper acetate was added under stirring, followed by slow dropwise addition of 5 mL of tert-butyl peroxide (TBHP, 70% aqueous solution), which was completed within 30 min. The reaction was carried out at 80-90° C. for 5 hours to obtain a polymer monomer as shown in formula (9).
[0092] S2 prepares a mixed solvent of ethylene carbonate and ethyl methyl carbonate in a ratio of 3:7, slowly adds lithium hexafluorophosphate to make the lithium salt concentration 1.2 mol / L, and stirs until the lithium salt is completely dissolved;
[0093] Next, 1 part of vinylene carbonate, 1 part of lithium difluorophosphate and 0.5 part of lithium difluorooxalatoborate were added to the electrolyte;
[0094] Then add 0.1 parts of thermal initiator azobisisobutyronitrile and stir thoroughly;
[0095] Finally, add 1.5 parts of the polymer monomer shown in formula (9), stir thoroughly to obtain a mixed solution;
[0096] S3 injects the mixed solution into the battery cell, and after standing for 45 hours, performs hot pressing for 0.5 hours at 85°C in a formation cabinet to initiate polymerization, and forms a gel in the battery cell.
[0097] The battery containing the gel electrolyte in step S2 is placed at room temperature and then subjected to conventional formation, i.e., charged at 0.1C current for 60 minutes, and then charged at 0.2C current to an upper voltage limit of 3.8V; the formed battery is subjected to high temperature aging at an aging temperature of 45°C for 24 hours.
[0098] After aging, vacuum pumping is performed with a vacuum degree of 88 kPa and a vacuum pumping time of 5 s. The film formation potential data is checked, the battery quality is checked, and the battery liquid absorption amount is estimated.
[0099] Finally, the battery is divided into different capacities, with the currents being 0.2C and 0.5C respectively. After two weeks of charge and discharge cycles, the battery manufacturing process is completed and a finished lithium-ion silicon negative electrode battery is obtained.
[0100] Example 2
[0101] S1 prepares a polymer monomer as shown in formula (2)
[0102] 1 mol of pentaerythritol, 4 mol of trimethylsilyl chloride, 1% p-toluenesulfonic acid and 2.5 ml of cyclohexane were added into the reactor and reacted at 85-90° C. for 6 h to generate trimethylpentaerythritol tetrapropylene silane product as shown in formula (2).
[0103] Add 1.5 parts of the polymer monomer shown in formula (2), stir thoroughly to obtain a mixed solution;
[0104] The remaining steps and parameters are consistent with those in Example 1.
[0105] Example 3
[0106] S1 prepares a polymer monomer as shown in formula (3)
[0107] 1 mol of pentaerythritol, 4 mol of triethyl chloroacetate silane, 1% p-toluenesulfonic acid and 2.5 ml of cyclohexane were added into the reactor and reacted at 85-90° C. for 6 h to generate trimethylpentaerythritol tetrapropylene silane product as shown in formula (3).
[0108] Add 1.5 parts of the polymer monomer shown in formula (3), stir thoroughly to obtain a mixed solution;
[0109] The remaining steps and parameters are consistent with those in Example 1.
[0110] Example 4
[0111] S1 prepares a polymer monomer as shown in formula (4)
[0112] 1 mol of pentaerythritol, 4 mol of tripropyl chloroacetate silane, 1% p-toluenesulfonic acid and 2.5 ml of cyclohexane were added into the reactor and reacted at 85-90° C. for 6 h to generate trimethylpentaerythritol tetrapropylene silane product as shown in formula (4).
[0113] Add 1.5 parts of the polymer monomer shown in formula (4), stir thoroughly to obtain a mixed solution;
[0114] The remaining steps and parameters are consistent with those in Example 1.
[0115] Example 5
[0116] S1 Preparation of polymer monomers as shown in formula (5)
[0117] 1 mol of pentaerythritol tetraacrylate is dissolved in 20 ml of water, and 4 mol of methoxytrimethylsilane is continuously dripped into the aqueous solution of pentaerythritol tetraacrylate, and the addition is completed within 30 minutes; in a water bath at 80° C., a 5% by mass ammonium persulfate solution is dripped, and the dripping speed is controlled to be completed in about 30 minutes, and the reaction is stirred at a constant temperature for 4 hours. The reaction is completed to obtain an organosiloxane-modified product as shown in formula (5).
[0118] Add 1.5 parts of the polymer monomer shown in formula (5), stir thoroughly to obtain a mixed solution;
[0119] The remaining steps and parameters are consistent with those in Example 1.
[0120] Example 6
[0121] S1 Preparation of a polymer monomer as shown in formula (6)
[0122] 1 mol of pentaerythritol tetraacrylate was dissolved in 20 ml of water, and 4 mol of methoxytriethylsilane was continuously dripped into the pentaerythritol tetraacrylate solution, and the addition was completed within 30 minutes; in a water bath at 80° C., a 5% ammonium persulfate solution was dripped, and the dripping speed was controlled to be completed in about 30 minutes. The reaction was completed by stirring at a constant temperature for 4 hours, and the organic siloxane-modified product shown in formula (6) was obtained.
[0123] Add 1.5 parts of the polymer monomer shown in formula (6), stir thoroughly to obtain a mixed solution;
[0124] The remaining steps and parameters are consistent with those in Example 1.
[0125] Example 7
[0126] S1 Preparation of polymer monomers as shown in formula (7)
[0127] 1 mol of pentaerythritol tetraacrylate was dissolved in 20 ml of water, and 4 mol of methoxytriethylsilane was continuously dripped into the pentaerythritol tetraacrylate solution, and the addition was completed within 30 minutes; in a water bath at 80° C., a 5% ammonium persulfate solution was dripped, and the dripping speed was controlled to be about 30 minutes. The reaction was completed by stirring at a constant temperature for 4 hours to obtain an organosiloxane-modified product as shown in formula (7).
[0128] Add 1.5 parts of the polymer monomer shown in formula (7), stir thoroughly to obtain a mixed solution;
[0129] The remaining steps and parameters are consistent with those in Example 1.
[0130] Example 8
[0131] S1 Preparation of a polymer monomer as shown in formula (8)
[0132] Dissolve 1 mol of pentaerythritol tetraacrylate in 20 ml of water, and continuously drip 4 mol of methoxytriisopropylsilane, i.e. ((CH3)2CH)3SiOCH3, into the pentaerythritol tetraacrylate solution within 30 minutes. In a water bath at 80°C, drip 5% ammonium persulfate solution at a rate of about 30 minutes. Stir at a constant temperature for 4 hours until the reaction is complete, and obtain an organosiloxane-modified product as shown in formula (8).
[0133] Add 1.5 parts of the polymer monomer shown in formula (8), stir thoroughly to obtain a mixed solution;
[0134] The remaining steps and parameters are consistent with those in Example 1.
[0135] Example 9
[0136] S1 prepares a polymer monomer as shown in formula (9), and the preparation method is consistent with Example 1.
[0137] Add 1 part of the polymer monomer shown in formula (9), stir thoroughly to obtain a mixed solution;
[0138] The remaining steps and parameters are consistent with those in Example 1.
[0139] Example 10
[0140] Add lithium hexafluorophosphate and lithium bis(trifluoromethanesulfonyl)imide in a ratio of 1:1 to make the concentration of lithium salt 1.2 mol / L, and stir until the lithium salt is completely dissolved;
[0141] Finally, add 1.5 parts of the polymer monomer shown in formula (2), stir thoroughly to obtain a mixed solution;
[0142] The remaining steps and parameters are consistent with those in Example 1.
[0143] Embodiment 11
[0144] Add 1.5 parts of a polymer monomer represented by formula (2) and a polymer monomer represented by formula (5) in a ratio of 1:1, stir well to obtain a mixed solution;
[0145] The remaining steps and parameters are consistent with those in Example 1.
[0146] Example 12
[0147] Add 1.5 parts of the polymer monomer represented by formula (9), the polymer monomer represented by formula (2) and the polymer monomer represented by formula (5) in a ratio of 1:1:1, stir well to obtain a mixed solution;
[0148] The remaining steps and parameters are consistent with those in Example 1.
[0149] Comparative Example 1
[0150] 1.5 parts of pentaerythritol tetraacrylate, a polymer monomer without an R group, was added and stirred thoroughly to obtain a mixed solution; the remaining steps and parameters were the same as those in Example 1.
[0151] The structure of the polymer monomer pentaerythritol tetraacrylate without an R group is shown in formula (10):
[0152]
[0153] Comparative Example 2
[0154] Add 1.5 parts of polymer monomer diethylene glycol diacrylate, stir thoroughly to obtain a mixed solution;
[0155] The remaining steps and parameters are consistent with those in Example 1.
[0156] Comparative Example 3
[0157] The addition of polymer monomers and thermal initiators was omitted, and the remaining steps and parameters were consistent with those in Example 1.
[0158] The cells used in Examples 1 to 12 and Comparative Examples 1 to 3 are: positive electrode material ternary 811 (Rongbai Technology), negative electrode material S420A (B&T), and the separator is a polypropylene separator. The electrolyte provided in the present invention is not only suitable for S420A negative electrode, but also has the effect of protecting the particle surface in negative electrodes with higher silicon content.
[0159] Performance Testing
[0160] The battery was charged and discharged at 1C at 25°C and 45°C, and its cycle times at room temperature and high temperature were tested. A high-temperature storage performance test was performed at 60°C, and the capacity retention rate, capacity recovery rate, and impedance growth rate for 7 days were tested. The test results are shown in Table 1.
[0161] 60℃ high temperature storage performance:
[0162] The divided battery was charged to 5V at 25°C with 1C constant current and constant voltage, with a cut-off current of 0.02C, and then discharged to 2.75V with 1C constant current, and the initial discharge capacity of the battery was measured. Then, the battery was charged to 5V with 1C constant current and constant voltage, with a cut-off current of 0.02C, and the initial volume of the battery was measured. Then, the battery was stored at 65°C for 14 days, and the thickness of the battery after storage at 65°C was measured. Then, the battery was discharged to 2.75V with 1C constant current, and the retention capacity of the battery was measured. Then, the battery was charged to 5V with 1C constant current and constant voltage, with a cut-off current of 0.02C, and then discharged to 2.75V with 1C constant current, and the recovery capacity was measured. The calculation formulas for capacity retention rate, capacity recovery rate, and impedance growth rate are as follows:
[0163] Capacity retention rate (%) = 100% × retention capacity / initial capacity
[0164] Capacity recovery rate (%) = 100% × recovery capacity / initial capacity
[0165] Impedance growth rate (%) = 100% × (impedance after test - impedance before test) / impedance before test
[0166] Table 1 Battery performance test results of the embodiments and comparative examples
[0167]
Claims
1. A lithium ion gel electrolyte, characterized in that: The invention comprises the following raw materials in parts by weight: Wherein, the polymer monomer structure is shown in formula (1): R includes -F, -OSi(C n H 2n+1 )3 or -Si(C m H 2m+1 ) One or more of 3; n=1~3, m=0~3.
2. The lithium ion gel electrolyte according to claim 1, characterized in that The polymer monomer is at least one of the following compounds:
3. The lithium ion gel electrolyte according to claim 1, characterized in that In the polymer monomer structure, n=1, m=1.
4. The lithium ion gel electrolyte according to claim 1, characterized in that The lithium salt includes one or more of lithium bis(trifluoromethanesulfonyl)imide, lithium bis(trifluorophosphoryl)imide, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorophosphate, lithium hexafluorophosphate or lithium tetrafluoroborate; The organic solvent includes one or more of ethylene carbonate, propylene carbonate, dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate, ethyl acetate, ethyl propionate, 1,3-dioxolane, 4-methyl-1,3-dioxolane, 1,2-dimethoxyethane, acetone, acetonitrile, methyl acetate, ethyl acetate, methyl propionate, tetrahydrofuran or 2-methyltetrahydrofuran; Preferably, the organic solvent comprises ethylene carbonate and ethyl methyl carbonate; Preferably, the organic solvent comprises ethylene carbonate and ethyl methyl carbonate in a ratio of 3:
7.
5. The lithium ion gel electrolyte according to claim 1, characterized in that The film-forming agent includes one or more of vinylene carbonate, fluoroethylene carbonate, 1,3-propane sultone, lithium difluorophosphate or lithium difluorooxalatoborate; the thermal initiator includes any one or more of azobisisobutyronitrile, dibenzoyl peroxide, di(4-tert-butylcyclohexyl) peroxydicarbonate, dodecanoyl peroxide or diisopropyl peroxydicarbonate.
6. The method for preparing a lithium ion gel electrolyte according to claims 1 to 5, characterized in that: The preparation method comprises: S1 Preparation of polymer monomers In a three-necked flask, an organic solvent, pentaerythritol tetraacrylate and sodium trifluoromethanesulfinate are added in sequence, and then copper salt is added under stirring, followed by slow dropwise addition of tert-butyl peroxide (TBHP, 70% aqueous solution), which is completed within 30 minutes. The reaction is carried out at 80-90° C. for 5 hours to obtain a polymer monomer as shown in formula (9); Add pentaerythritol into a reactor, then add trimethyl silyl chloride, triethyl silyl chloride or tripropyl silyl chloride, add p-toluenesulfonic acid and cyclohexane as catalysts, and react at 85-90° C. to generate trimethyl pentaerythritol tetrapropylene silane product, as shown in formula (2), formula (3) or formula (4); (CnH 2n+1 )3SiOCH3 is continuously dripped into the aqueous solution of pentaerythritol tetraacrylate, and then ammonium persulfate solution is added in a water bath at 80°C, and the dripping speed is controlled to be completed in about 30 minutes, and the mixture is stirred at a constant temperature for 4 hours. The reaction is completed to obtain an organosiloxane-modified product, as shown in formula (5), formula (6), formula (7) or formula (8); (CnH 2n+1 )3SiOCH3 includes methoxytrimethylsilane, methoxytriethylsilane, methoxytriethylsilane or methoxytriisopropylsilane; S2 dissolving lithium salt, film-forming agent, thermal initiator and polymer monomer in an organic solvent to obtain a mixed solution; S3 injects the mixed solution into the battery cell, and after standing still, performs heat pressing to initiate polymerization.
7. The method for preparing a lithium ion gel electrolyte according to claim 6, characterized in that: The standing time is 40 to 50 hours; the hot pressing polymerization is carried out in a chemical forming cabinet at 70 to 90° C. for 0.2 to 1 hour.
8. The use of the lithium ion gel electrolyte according to any one of claims 1 to 5, characterized in that: The lithium ion gel electrolyte can be used to prepare silicon negative electrode batteries.
9. The use of the lithium ion gel electrolyte as claimed in claim 8, characterized in that: The process of preparing silicon negative electrode battery includes: The battery containing the gel electrolyte in the cell of step S3 is placed at room temperature and then subjected to conventional formation, high temperature aging, vacuum pumping and capacity separation, and finally battery packaging to obtain a finished lithium-ion silicon negative electrode battery.
10. The use of the lithium ion gel electrolyte according to claim 9, characterized in that: Conventional formation includes charging at 0.1C current for 60 minutes, and then charging at 0.2C current to the voltage upper limit of 3.8V; the aging temperature is 40-50°C, the time is 20-30 hours, the vacuum degree of vacuum pumping is 70-100kPa, and the vacuum pumping time is 3-10s.
Citation Information
Cited By
Preparation method of fluorine-containing ion gel
CN120690908A